2017
DOI: 10.1371/journal.pone.0181905
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of self-collected vaginal dry swabs using the Xpert human papillomavirus assay

Abstract: BackgroundPolymerase chain reaction-based Xpert human papillomavirus (HPV) assay is a rapid test that detects high-risk HPV (hrHPV) infection. This point-of-care test is usually performed by collecting a cervical specimen in a vial of PreservCyt® transport medium. We compared HPV test positivity and accuracy between self-collected sample with a dry swab (s-DRY) versus physician-collected cervical sampling using a broom like brush and immediate immersion in PreservCyt (dr-WET).MethodsIn this cross-sectional stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Across all assays, the V specimen had high sensitivity, specificity and predictive value for this clinical end point, and performed similarly to the technical reference standard that was built from a clinician-collected cervical specimen. Our findings are comparable to those of a recent pilot study in Geneva among 150 women known to have previous abnormal cytology where they investigated Xpert HPV using selfcollected specimens for the detection of stage 2 cervical intraepithelial neoplasia or worse and found moderately high sensitivity and PPV for this outcome (>84%), but lower specificity and NPV (<50%) compared with the current study, for reasons that are unclear [15]. Furthermore, in the Geneva pilot study, cliniciancollected specimens were only used for cytology and did not undergo HPV testing.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Across all assays, the V specimen had high sensitivity, specificity and predictive value for this clinical end point, and performed similarly to the technical reference standard that was built from a clinician-collected cervical specimen. Our findings are comparable to those of a recent pilot study in Geneva among 150 women known to have previous abnormal cytology where they investigated Xpert HPV using selfcollected specimens for the detection of stage 2 cervical intraepithelial neoplasia or worse and found moderately high sensitivity and PPV for this outcome (>84%), but lower specificity and NPV (<50%) compared with the current study, for reasons that are unclear [15]. Furthermore, in the Geneva pilot study, cliniciancollected specimens were only used for cytology and did not undergo HPV testing.…”
Section: Discussionsupporting
confidence: 83%
“…The use of point-of-care HPV testing is one such approach. This study adds to a growing body of evidence demonstrating that hrHPV testing can be offered at point-of-care with minimal need for speculum examinations for women, to guide same-day clinical management for cervical cancer prevention [6,7,15].…”
Section: Discussionmentioning
confidence: 94%
“…This update contains 19 new reports containing 22 diagnostic studies and nine new randomized participation trials, 26 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 which were added to the 34 accuracy studies and to the 16 participation trials already included in the previous meta-analyses. 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 99 100 101 102 103 104 105 106 107 108 109 110 111 112 113 114 115 116 117 The updated meta-analyses finally comprised 56 diagnostic test accuracy studies a...…”
Section: Resultsmentioning
confidence: 99%
“…New technologies in cervical cancer screening have been proposed to directly benefit high-risk populations [18]. Several studies showed the safety of self-collection compared to the clinician-collected cervical samples [1416,1921] and the improved performance of a primary HPV test in early detection of HSIL compared with negative cytology [2226]. HPV-DNA molecular testing coupled with samples obtained by CVSC is a valid alternative to be considered in the practice of cervical cancer screening in the Tapajós region, because of the ease and feasibility both for women who routinely attend clinics, such as HIV-infected women, and those who undergo it for the first time or less regularly, such as those from our study.…”
Section: Discussionmentioning
confidence: 99%